Hollow-microsphere composite offers depth-independent superior thermal insulation for diver suits. (13th February 2019) - Brown, Jonathan; Oldenkamp, John; Gamache, Raymond; Grbovic, Dragoslav; Kartalov, Emil
Abstract: We present an experimental proof of principle for a composite material to be used for diver suit insulation. Traditional suits are made of foamed neoprene, which shrinks with increasing pressure at depth under water, leading to a loss in thermal protection for the diver. Our experiments show that the insulance of neoprene from a top-of-the-line 8 mm suit drops by ∼52% at 57 psi added pressure (equivalent to 128 FSW depth). In contrast, the insulance of our composite is higher than neoprene's at atmospheric pressure and drops by ∼1% at the same 57 psi added pressure. The composite is made of 3 M K1 air-filled glass microspheres embedded in Sylgard 184 silicone. The more than twice better thermal performance of the composite compared to neoprene suggests that there will be a corresponding increase in the persistence time of divers equipped with composite suits. COMSOL theoretical calculations agree with our experimental results, while SEM images of the composite confirm that there is no significant breakage of microspheres during material fabrication. Our results show that the microsphere composite is an excellent candidate to replace bubbled neoprene in diver suits.